Keunikan Gereja Tubuh Kristus dalam Terminologi Misi dan Teologi Paulus - Harefa, Darmianus; Tengkue, Anggreini Angelina (Program Studi Misiologi dan Komunikasi Kristen, 2023)
The purpose of this research is to see the uniqueness of the concept of the church and the concept of the mission of the body of Christ discussed in Paul's theology. This research uses descriptive qualitative research methods, with the aim of explaining the concept of the church as the body of Christ sourced from articles and books that discuss this concept. So that the result is that Paul discusses the concept of the body of Christ in more depth in Romans, 1 Corinthians, Colossians and Ephesians. This term is based on the concept of